Impactos de diluições de efluente da aquicultura na vazão de gotejadores não autocompensantes operando em bancadas experimentais - Souza, Ana Luiza Veras de (Universidade Federal Rural do Semi-Árido, 2021)
Aquaculture is an activity that enables the benefit of creating multiple aquatic species in a single space, however, promotes the Generation of effluents with considerable amounts of organic and metabolic waste, capable of interfering with the flow of emitters. Thus, the objective of this work was to analyze the effects of aquaculture effluent (AE) dilutions in well water (WW) on the performance of dripping units. For this purpose, five drip units were set up in an experimental area of the Universidade Federal Rural do Semi-Árido, in Mossoró-RN, equipped with three types of non-self-compensating emitters (Netafim Super Typhoon-ST, Netafim Streamline-SL and Naan DanJain TalDrip-DT). Five were applied dilutions of AE in WW (D1 - 100% of WW plus 0% of AE; D2 - 75% of WW plus 25% of AE; D3 - 50% of WW plus 50% of AE; D4 - 25% of WW plus 75% of AE; and D5 - 0% of WW plus 100% of AE). At evaluation times 0 and 20 h, the flow rate measurement of 16 drippers per line was performed, in three repetitions, the length of the lateral lines was 8 m. Descriptive statistics (mean, standard deviation and coefficient of variation) were used to interpret the flow rate data. At 0 h, the physicochemical and microbiological characterization of the AE dilutions was carried out. The highest values of standard deviation and coefficient of variation occurred in the D2 dilution, when analyzing the flow rate data from the operating times of 0 and 20h; while the lowest values were reached in the D1 dilution; the SL emitter presented the lowest values of standard deviation and coefficient of variation in relation to the ST and DT emitters in all studied dilutions. Comparing the dilutions D1 to D5, in the operating times of 0 and 20h, an increase in flow rate was evidenced in the three emitters, due to the fact that it is in the initial phase of clogging where there is oscillation in the flow rate values; and the attributes of the AE dilutions that presented severe risk of emitter obstruction were the total dissolved solids in D1, pH in D2, D3, D4 and D5 and magnesium in D1, D2 and D3
Keywords: Água residuária; Reúso; Desempenho hidráulico; Obstrução de emissores; Água residuária; Reúso; Desempenho hidráulico; Obstrução de emissores; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA